New ages and chemical analysis on Lower Jurassic volcanism close to the dorsal de Huincul, Neuquén - Schiuma, Mario (2008)
New single zircon ages from hydrocarbon well cores in the A-1 Norte de la Dorsal and Anticlinal Campamento area of the Neuquén basin indicate that 199.0 ± 1.5 Ma andesite lava flow and 203.75 ± 0.26 Ma dacite breccia overlie a 286.5 ± 2.3 Ma granodiorite and 284.0 ± 1.3 Ma andesite dike. The Lower Jurassic volcanics were deposited on a regional erosion surface affecting the Permian rocks. In the studied area there is no record of Middle to Upper Triassic volcanics as in other areas of the basin. Exotic zircon crystals gave ages of Mesoproterozoic, Middle Cambian, Early Devonian and Early Carboniferous, suggesting a poliphasic basement. Chemical analyses of three selected samples show a calc-alkaline signature, supporting the existence of a volcanic arc at the Early Jurassic as it has been proposed for the center of the basin.